Art For Africa’s Sake: The African Novel And Literary Criticism - Dida, Nassireddine (University of El-oued, 2021)
Abstract The current paper discusses the relevance of the principles of aestheticism to the African novel. Drawing on some ideas expressed by Fredric Jameson in his book The Political Unconscious, this article argues that the claim of an autonomous art is yet another ideology spread to bury the history of colonialism, oppression and suppression. The literature of the colonised countries tends to maintain a political atmosphere that reflects ideological conflicts or tensions. Nevertheless, when a novel is overwhelmed by political thoughts, or represents them, it does not seem to appeal to the Western world - that is, not aesthetically mature enough. If universal or conventional standards of writing novels warn against political indoctrination, on account of being very subjective and biased, does this mean that African writers must give up writing about their own countries or beliefs to be accepted as good writers? What is the true object of literature if it does not voice the nationalist sentiment of the colonised?
Article .Ex Professo. Vol 06. N 01. Université d'El-Oued
Keywords: Keywords: Aestheticism; African Novel; Colonialism; Ideology; Literature; Literary Criticism.